“Art and Doucmentaries in Climate Communication": A Review and Participant-Voiced Poetic Inquiry - Mullooly, Sheila C. (Art/Research International, 2022)
The following is a review, participant-voiced poetic inquiry, and commentary on the article, “Art and Documentaries in Climate Communication: Experiencing the Reality of Climate Change and Leading the Way to Change.” Liselotte Roosen and Christian Klockner (2020) published this case study as part of a more extensive research project, Climart, funded by the Norwegian Research Council. In this review, I consider the relationships between artworks, researchers, and audience participants. I offer a participant-voiced poetic inquiry of the arts-based research project. I address the project’s goals for social/political/cultural change, its local and global contexts, and future implications.